Attracting Chinese Tourists to Finland - Popov, Aleksei (2020)
The aim of this thesis is to research development of Chinese outbound tourism market and buying behavior of Chinese tourists. The target of this research is to define the best ways of attracting Chinese tourists to the regions of Lakeland and North Karelia in Finland. The suggestions for possible improvements in the regions’ tourism image are determined. The research utilizes numerous sources of secondary data in forms of academic publications, business reports, statistics and electronic databases. The primary data for the research is taken from survey of 70 respondents conducted face-to-face in two cities in China. Besides that, numerous interviews of industry experts are carried out through phone calls or online. The results of this research reveal that the regions of Lakeland and North Karelia in Finland have a potential of better development as a destination for rapidly growing Chinese outbound tourism market. The areas suggested for further development are Educational Tourism and Health Tourism.